Neoadjuvant immunochemotherapy improves clinical outcomes of patients with esophageal cancer by mediating anti-tumor immunity of CD8+ T (Tc1) and CD16+ NK cells - He, Yunlong; Yang, Depeng; Lin, Xiaoyu; Zhang, Jinfeng; Cheng, Rui; Cao, Liangyu; Yang, Lijun; Zhang, Mengmeng; Shi, Xinyue; Jin, Xiyun; Sun, Handi; Sun, Haoxiu; et al. (Frontiers in Immunology, 2024)
Background: Esophageal cancer (ESCA) is one of the most common tumor in the world and the treatment is still unsatisfied applied with neoadjuvant therapy (NT) based on the radiotherapy and/or chemotherapy. Neoadjuvant immunochemotherapy (NICT) has also become an effective treatment strategy nowadays. However, its impact on the tumor microenvironment (TME) and regulatory mechanisms on T cells and NK cells need to be further elucidated. Methods: We collected 279 cases of ESCA who underwent surgery alone (non-neoadjuvant therapy, NONE), neoadjuvant chemotherapy (NCT) and NICT, respectively, and compared their therapeutic effect and survival period. Further, RNA sequencing combined with biological information were used to analyze the expression of immune-related genes. Immunohistochemistry, immunofluorescence, and quantitative real-time PCR (qRT-PCR) were used to verify the activation and infiltration status of CD8+ T and CD16+ NK cells, as well as the function and regulatory pathway of killing tumor cells. Results: Patients with ESCA in the NICT group showed better clinical response, median survival and two-year survival rates (p<0.05) compared with the NCT group. Our RNA sequencing data revealed that NICT could promote the expression of immune-related genes. And the infiltration and activation of immune cells were significantly enhance centered with CD8+ T cells. CD8+ T cells activated by PD-1 inhibitors secreted more IFN-γ and cytotoxic effector factors cells through the transcription factor of EOMEs and TBX21. At same time, activated CD8+ T cells mediated the CD16+ NK cells activation and secreted more IFN-γ to kill EC cells. In addition, the immunofluorescence co-staining results showed that more CD276+ tumor cells and CD16+ NK cells were exited in pre-NCT and pre-NICT group. But CD276+ tumor cells were reduced significantly in post-NICT group while it was still occurred in post-NCT group, which means CD16+ NK cells can recognize and kill CD276+ tumor cells after ICBs treat Conclusion: NICT can improve therapeutic effect and survival period of resectable ESCA patients. NICT could promote the expression of immune-related genes and active CD8+ T and CD16+ NK cells to secrete more IFN-γ to kill ESCA cells. It provide theoretical basis and clinical evidence for its potential as a NT strategy in ESCA.